Self-assembled peptide nanorod vaccine confers protection against influenza A virus. (February 2021) - Zottig, Ximena; Al-Halifa, Soultan; Côté-Cyr, Mélanie; Calzas, Cynthia; Le Goffic, Ronan; Chevalier, Christophe; Archambault, Denis; Bourgault, Steve
Abstract: Proteinaceous nanostructures have emerged as a promising strategy to develop safe and efficient subunit vaccines. The ability of synthetic β-sheet self-assembling peptides to stabilize antigenic determinants and to potentiate the epitope-specific immune responses have highlighted their potential as an immunostimulating platform for antigen delivery. Nonetheless, the intrinsic polymorphism of the resulting cross-β fibrils, their length in the microscale and their close structural similarity with pathological amyloids could limit their usage in vaccinology. In this study, we harnessed electrostatic capping motifs to control the self-assembly of a chimeric peptide comprising a 10-mer β-sheet sequence and a highly conserved epitope derived from the influenza A virus (M2e). Self-assembly led to the formation of 100–200 nm long uniform nanorods (NRs) displaying the M2e epitope on their surface. These cross-β assemblies differed from prototypical amyloid fibrils owing to low polydispersity, short length, non-binding to thioflavin T and Congo Red dyes, and incapacity to seed homologous amyloid assembly. M2e-NRs were efficiently uptaken by antigen presenting cells and the cross-β quaternary architecture activated the Toll-like receptor 2 and stimulated dendritic cells. Mice subcutaneous immunization revealed a robust M2e-specific IgG response, which was dependent on self-assembly into NRs. Upon intranasal immunization in combination with the polymeric adjuvant montanide gel, M2e-NRs conferred complete protection with absence of clinical signs against a lethal experimental infection with the H1N1 influenza A virus. These findings indicate that by acting as an immunostimulator and delivery system, synthetic peptide-based NRs constitute a versatile self-adjuvanted nanoplatform for the delivery of subunit vaccines. Graphical abstract: Image 1